COVID-19 epidemic: Proposed alternatives in the management of digestive cancers: A French intergroup clinical point of view (SNFGE, FFCD, GERCOR, UNICANCER, SFCD, SFED, SFRO, SFR). Issue 6 (June 2020) - Di Fiore, Frederic; Bouché, Olivier; Lepage, Come; Sefrioui, David; Gangloff, Alice; Schwarz, Lilian; Tuech, Jean Jacques; Aparicio, Thomas; Lecomte, Thierry; Boulagnon-Rombi, Camille; Lièvre, Astrid; Manfredi, Sylvain; et al.
Abstract: Introduction: Patients treated for malignancy are considered at risk of severe COVID-19. This exceptional pandemic has affected countries on every level, particularly health systems which are experiencing saturation. Like many countries, France is currently greatly exposed, and a complete reorganization of hospitals is ongoing. We propose here adaptations of diagnostic procedures, therapies and care strategies for patients treated for digestive cancer during the COVID-19 epidemic. Methods: French societies of gastroenterology and gastrointestinal (GI) oncology carried out this study to answer two main questions that have arisen (i) how can we limit high-risk situations for GI-cancer patients and (ii) how can we limit contact between patients and care centers to decrease patients' risk of contamination while continuing to treat their cancer. All recommendations are graded as experts' agreement according to the level of evidence found in the literature until March 2020. Results: A proposal to adapt treatment strategies was made for the main GI oncology situations. Considering the level of evidence and the heterogeneous progression of the COVID-19 epidemic, all proposals need to be considered by a multidisciplinary team and implemented with patient consent. Conclusion: COVID-19 epidemic may significantly affect patients treated for digestive malignancies. Healthcare teams need to consider adapting treatment sequences when feasible and according to the epidemic situation.